Kalibrasi Single-Normal Hot-Wire Probe Sigmond Cohn Alloy 851 untuk Aliran Jet Terpulsasi - Klaus Bremhorst; Hariyo Priambudi Setyo Pratomo (Institute of Research and Community Outreach, Petra Christian University, 2006)
Calibration of a Sigmond Cohn alloy 851 single normal hot-wire probe was performed with a stationary calibration method with a range of nozzle exit velocity from 2 up to 80 m/s. The calibration aims to determine the best calibration response equation associated with the accuracy of curve fit. The curve fit accuracy test shows that the extended power-law equation provides a better curve fit than the simple power-law equation. A look-up table method used can improve the accuracy of curve fit of the extended power-law equation from a ± 1.7 % into  0.03% accuracy. Uncertainty analysis of root mean square value meets criteria of 4% error. Abstract in Bahasa Indonesia : Kalibrasi single-normal hot-wire probe Sigmond Cohn alloy 851 dilakukan dengan metode kalibrasi stasioner pada rentang kecepatan exit nozzle 2 sampai 80 meter/detik. Kalibrasi ini bertujuan untuk menentukan persamaan respon kalibrasi yang paling baik yang dinyatakan dengan akurasi curve fit. Dari hasil pengujian akurasi curve fit%2C persamaan extended power-law memberikan curve fit yang lebih baik daripada curve fit yang dihasilkan oleh persamaan simple power-law. Metode look-up table yang digunakan dapat meningkatkan akurasi curve fit persamaan extended power-law dari ± 1.7 % menjadi  0.03%. Analisis ketidakpastian dari root mean square memenuhi kriteria 4% error. Single normal hot-wire probe%2C stationary calibration method%2C extended power-law equation%2C simple power-law equation%2C look-up table method.